PSYCHOLOGICAL CAPITAL AS A MODERATOR IN TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE IN HEALTHCARE - Haryanto , Bambang; Suryanto; Lestari , Yetty Dwi; Musa , Kazi (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The background of this study is based on the challenges faced by the hospital industry in improving employee productivity, primarily through effective leadership and a conducive organizational culture. However, the moderating role of psychological Capital in this relationship remains unclear, especially in healthcare. This study investigates the interplay between transformational leadership, organizational culture, psychological Capital, and employee productivity in the hospital industry. This study employs quantitative methods, specifically the Structural Equation Modeling (SEM) approach, using SmartPLS software. The research data were collected through a survey of employees in several large hospitals, with a sufficient number of respondents who were statistically representative. The study results indicate that organizational culture significantly mediates the relationship between transformational leadership and employee productivity. At the same time, psychological Capital does not play an essential role as a moderator in this relationship. These findings highlight the significant role of organizational culture as a crucial link between transformational leadership style and enhanced employee productivity. In practice, the results of this study provide recommendations for hospital management to strengthen transformational leadership development programs that foster a collaborative, innovative, and employee-involved organizational culture. The limitations of this study lie in the cross-sectional design used and the limited geographic and organizational context. We recommend conducting further research using a longitudinal approach and expanding the research context to enhance the generalizability of the findings. JEL Classification Codes: I19, M12, M54.